Stakeholder Analysis on Indonesian E-Commerce Taxation - Amelia Setiawan; Sylvia Fettry Elvira Maratno; Puji Astuti Rahayu; Monica Paramita Ratna Putri Dewanti (Universitas Prasetiya Mulya, 2019)
Trade industry had been effected significantly by the high pace of digitalization. The growth level of Indonesian online trading activities is predicted to be extremely high because of the huge number of internet users in Indonesia. This is perceived as a great chance to enter the online commercial trading market in Indonesia. The interactive online marketplace makes it easy to buy and sell goods and services more efficiently in everywhere and at any time. However, there is little consideration on the taxation aspect of e-commerce transaction in Indonesia as developing country. This study gives an analysis on Indonesian e-commerce taxation based on identified main group of stakeholders. The literature review is conducted to get comprehensive understanding on common e-commerce taxation. The analysis of e-commerce taxation grasps the comparison of practices between developed and developing countries.Keywords:Taxation, E-commerce, Stakeholder Analysis* Accounting Department, Faculty of Economics, Parahyangan Catholic University, Gedung 9, Jl. Ciumbuleuit 94, Bandung 40141, Indonesia. https://doi.org/10.21632/irjbs.12.3.277-288